Effect of long-term partial bladder outlet obstruction on caldesmon isoforms and their correlation with contractile function - Yang Lin; He Da-lin; Wang Shu; Cheng He-peng; Wang Xin-yang (Acta Pharmacologica Sinica, 2016)
Aim: In the present study, we investigate the expression of caldesmon (CAD) isoforms in rabbit detrusor smooth muscles (DSM) during the progression of partial bladder outlet obstruction and relate them with the time course of obstruction. Methods: Detrusor samples were obtained from the bladders of rabbits with partial bladder outlet obstruction and sham-operated control rabbits after 1, 2, 4, and 8 weeks of obstruction. Contractile responses to field stimulation and carbachol were determined in the isolated bladder strips. Western blotting was used to determine the relative levels of CaD isoform expression at the protein levels. Results: The contractile responses decreased progressively over the course of obstruction. The expression of l-CaD increased significantly to approximately the same extent as the 1–4-week obstructed groups and further in the 8-week obstructed group. The expression of h-CaD increased in all of the obstructed bladders, but at significantly higher levels in the 1–2-week obstructed bladders compared to the control and 4–8-week obstructed bladders. Conclusions: The changes in the isoforms of CaD may be part of the molecular mechanism for bladder compensation following partial bladder outlet obstruction. The overexpression of l-CaD and the h-CaD/l-CaD ratio could be markers for the status of DSM remodeling and dysfunction.